Social Support and Mental Health: The Moderated-Mediator Impact of Resilience and Education Level among New Boarding School Students - Ni'maturrohmah, Elis; Wibowo, Mungin Eddy; Sunawan, Sunawan (Universitas Negeri Semarang, 2023)
Mental health is considered important to adaptation, stress management and Islamic boarding school students (santri) resilience in coping with problems. Thus, this present research aimed at analyzing the relationship between social support and mental health through resilience in the first-year students at junior high school and senior high school, namely grade seven and grade ten in Bojonegoro Regency. Here, 331 freshmen were selected using a cluster random sampling technique. Their data of mental health, social support, and resilience were collected using Mental Health Inventory (MHI), The Multidimensional Scale of Perceived Social Support (MSPSS) and Connor-Davidson Resilience Scale (CD-RISC). The findings showed there was a positive relationship between social support and mental health through resilience. In addition, the moderating effect of education level explained that the relationship between resilience and mental health tended to be stronger for freshmen at the junior high school level. Further implications are presented in the discussion session.